DESEMPENHO DE SISTEMAS PREDIAIS: AVALIAÇÃO DE RUÍDO EM EDIFÍCIOS RESIDENCIAIS - Bleichvel, Natália Cristina Thiem; Kalbusch, Andreza; Iafigliola, Leandro Giamas (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The growth of civil construction potential has made buildings the main housing solution. As the space is divided by numerous families, the acoustic comfort in the housing units sometimes proves insufficient. The noise propagation in plumbing systems due to vibration of water or sewage flow through the pipe may be cause of discomfort for users. Since the creation of the performance standard in residential buildings, ABNT NBR 15575, residential buildings must comply with a series of quality criteria. This research studies the principles of acoustics in buildings, with a focus on plumbing systems noise. In addition, the objective was to perform a comparative analysis between buildings with different finishing pattern, involving the measurement of plumbing systems noise. In the case study, the noise caused by the operation of plumbing fixtures in buildings classified as simple finishing pattern was higher than the noise measured in similar conditions in buildings classified as medium and higher pattern.